IMPACT OF MACROECONOMIC EFFECTS GENERATED BY FOREIGN HEALTH TOURISTS IN THE PERIOD 2017-2020 - Nagy, Tamás; Sáránszki, Lili; Baumann, Lilla Tünde; Bátor, Gábor László (Stadium - Hungarian Journal of Sport Sciences, 2023)
Health tourism is one of the defining sectors of the global economy; its growing trend exceeds the growth rate of the world GDP. As a result of the COVID-19 pandemic, tourism and, as part of it, the health tourism sector has become almost impossible. Our research aimed to examine the demand of tourists coming to Hungary for health tourism in the period 2017-2020. Our further goal was to quantify the magnitude of the macroeconomic effects generated by the consumption of foreign health tourists and their evolution in 2017-2020. The basic information of the secondary research was the tourism demand data published by the Central Statistical Office. The KSH data comes from a collection called "Tourist and other expenses of foreigners in Hungary." The information used was downloaded from the KSH Information database. Due to the COVID-19 epidemic, there was a significant decrease in foreign tourist arrivals. The year before the epidemic (2019) was already characterized by a decline in the number of guest nights spent by tourists coming to our country due to wellness tourism and medical interventions. Still, the pandemic resulted in a drastic decrease. Between 2017 and 2019, there was an increase in the national economic effects, and in 2020 there was a significant decline in the number of tourists coming to our country for health tourism from abroad. Due to the COVID-19 pandemic and related restrictions, the proportion of tourists coming from abroad for health tourism has drastically decreased, as well as the total amount of goods they spend in our country. As a result, our country's economic income from health tourism has significantly decreased.